Camptocormia Induced by a Dopaminergic Agonist. Issue 2 (March 2018) - Mano, Tomoo
Abstract : Abstract: Camptocormia, a condition that involves the abnormal flexion of the trunk and results in a forward-bending posture, is relatively common during the course of Parkinson disease (PD). Despite this, there is ongoing controversy concerning its mechanisms and no consensus regarding the underlying etiology. This report demonstrates a case in which a dopaminergic agonist (DA) was implicated in the onset of camptocormia episodes in a non-PD patient who developed camptocormia after the start of DA treatment. Over a course of 8 years, the patient experienced intermittent camptocormia, which resulted in multiple falls. After cessation of the DA, the patient showed decreased camptocormia symptoms. This case report suggests that clinicians should consider the possibility of DA-induced camptocormia in patients with PD and non-PD patients receiving DA treatments, and serves to caution clinicians regarding the administration of DAs.